Cross-sectional examination of the association between shift length and hospital nurses job satisfaction and nurse reported quality measures - Jane Ball; Tina Day; Trevor Murrells; Chiara Dall'Ora; Anne Marie Rafferty; Peter Griffiths; Jill Maben (BMC, 2017)
Abstract Background Twenty-four hour nursing care involves shift work including 12-h shifts. England is unusual in deploying a mix of shift patterns. International evidence on the effects of such shifts is growing. A secondary analysis of data collected in England exploring outcomes with 12-h shifts examined the association between shift length, job satisfaction, scheduling flexibility, care quality, patient safety, and care left undone. Methods Data were collected from a questionnaire survey of nurses in a sample of English hospitals, conducted as part of the RN4CAST study, an EU 7th Framework funded study. The sample comprised 31 NHS acute hospital Trusts from 401 wards, in 46 acute hospital sites. Descriptive analysis included frequencies, percentages and mean scores by shift length, working beyond contracted hours and day or night shift. Multi-level regression models established statistical associations between shift length and nurse self-reported measures. Results Seventy-four percent (1898) of nurses worked a day shift and 26% (670) a night shift. Most Trusts had a mixture of shifts lengths. Self-reported quality of care was higher amongst nurses working ≤8 h (15.9%) compared to those working longer hours (20.0 to 21.1%). The odds of poor quality care were 1.64 times higher for nurses working ≥12 h (OR = 1.64, 95% CI 1.18-2.28, p = 0.003). Mean 'care left undone' scores varied by shift length: 3.85 (≤8 h), 3.72 (8.01-10.00 h), 3.80 (10.01-11.99 h) and were highest amongst those working ≥12 h (4.23) (p < 0.001). The rate of care left undone was 1.13 times higher for nurses working ≥12 h (RR = 1.13, 95% CI 1.06-1.20, p < 0.001). Job dissatisfaction was higher the longer the shift length: 42.9% (≥12 h (OR = 1.51, 95% CI 1.17-1.95, p = .001); 35.1% (≤8 h) 45.0% (8.01-10.00 h), 39.5% (10.01-11.99 h). Conclusions Our findings add to the growing international body of evidence reporting that ≥12 shifts are associated with poor ratings of quality of care and higher rates of care left undone. Future research should focus on how 12-h shifts can be optimised to minimise potential risks.